Pengendalian Penyakitlayu Pisang Dengan Fusarium Nonpatogenik Dan Fluorescent Pseudomonads - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2007)
The study was aimed to know the ability ofjluorescent pseudomonads and nonpathogenic Fusarium for controlling fusarium wilt of banana. The research was conducted both in the laboratory and glass house in the Faculty of Agriculture Gadjah Mada University. Laboratorial trial included the examining of antagonistic capacity in vitro and the population of these two antagonistic microorganisms in compost medium. The examination of the effect of these two microorganisme in compost medium against fusarium wilt of banana Ambon Kuning cultivar was conducted in a glass house. The result showed that there was no antagonistic mechanism occurred between fluorescent pseudomonads and nonpathogenic Fusarium. The treatment of compost withjluorescent pseudomonads or/and nonpathogenic Fusarium showed that there were differences on the optimum population of these two antagonistic microorganisms. Fluorescent paseudomonads attained its optimum population one week after inoculation while nonpathogenic Fusarium attained its optimum population two weeks after inoculation. The glass house trial showed that compost enriched with two microorganism with one week incubation time reduced percentage of wilted leaves, althought it was nonsignificant with control treatment. Field experiment should be conducted with higher popupation density of antagonist microorganisms